(untitled) (Szociológiai Szemle, 2024)
The paper investigates some hidden trends in East-Central European economic sociology and the recent challenges they have to face with. It argues that Western economic sociology is „paradigm-oriented", while these kind of researches are „problem-orinted” in East-Central Europe. Social facts don’t have simple illustrative fuction in their case. Their primary aim is invariably to understand, describe and explain relevant social aspects of econimic life: the nature of institutional changes, the recruitment, motives and attitudes of old and new economic actors. Most of these disperse researches are empirically established, sensitive, but underconceptualized attempts. Therefore their contribution to the recent paradigms is relatively weak, but they provide sets of provocative questions and may help to find the lost sociological imagination.